Community structure of heritable viruses in a Drosophila-parasitoids complex - Varaldi, Julien; Lepetit, David; Burlet, Nelly; Faber, Camille; Baretje, Bérénice; Allemand, Roland (Peer Community Journal)

(untitled)
The diversity and phenotypic impacts related to the presence of heritable bacteria in insects have been extensively studied in the last decades. On the contrary, heritable viruses have been overlooked for several reasons, including technical ones. This is regrettable because of the size of this gap knowledge and because case study indicate that viruses may have profound impact on the functionning of individuals and communities. Additionally, the factors that may shape viral communities are poorly known, except in some very specific viral-insect systems. Here we analyze the community structure of heritable viruses in a multi-hosts-multi-parasitoids community. Drosophilidae and their larval and pupal parasitoids were sampled in two locations, two years and two seasons. After two lab generations, putative DNA and RNA viruses were purified and sequenced. Our analysis revealed the presence of 53 viruses (including 37 new viruses), the great majority of which were RNA viruses. The "species" factor was by far the most significant one, explaining more than 50% of the variance in viral structure. Additionally, parasitoids had a higher number of heritable viruses compared to their hosts, suggesting that this lifestyle favours the association with viruses. Finally, our community-level survey challenged previous interpretation concerning the host range of some previously described viruses.